TRENDS OF DENGUE HEMORRHAGIC FEVER IN BAU BAU DISTRICT, SOUTHEAST SULAWESI PROVINCE, INDONESIA, 2009-2014 - Tosepu, Ramadhan (Public Health of Indonesia, 2017)
Objectives: To analyze trends of dengue hemorrhagic fever in Baubau district from 2009 to 2014Methods: We used the national data on annual reported cases from the Health Office Baubau and population data from Statistics of Baubau regency, 2009-2014.Results: The findings have shown a downward trend of the number of dengue cases. In 2009 the DHF cases were 117, decreased to 18 cases in 2010, and continued to decrease to 11 cases in 2011. While in 2012 the cases have increased to 45 cases, and steeply increased to 111 cases in 2013, but then in 2014 decreased to 79 cases.Conclusions: We conclude that the temporal tendency of DHF increases every March. This trend of dengue highlights the need for a more systematic surveillance and reporting of the disease.